Chlorpyriphos and T-2 Toxin Induced Haemato-Biochemical Alterations in Broiler Chicken - Krishnamoorthy, P.; Vairamuthu, S.; Balachandran, C.; Muralimanohar, B. (International Journal of Poultry Science, 2006)
The present work was undertaken to study the haematobiochemical changes in chlorpyriphos and T-2 toxin fed broiler chicken. Known amounts of chlorpyriphos and T-2 toxin containing powdered wheat substrates were incorporated into the toxin free broiler starter mash, singly and in combination to yield 45 ppm chlorpyriphos and 0.5 ppm T-2 toxin. Forty eight day-old broiler chicks were randomly allotted into four groups of 12 each i.e., control, chlorpyriphos, T-2 and chlorpyriphos+T-2 groups and fed with toxin mixed diets from 0 to 4 weeks of age and studied various haematobiochemical parameters on 14th and 28th day of age. PCV and Hb levels decreased significantly (P< 0.01) in toxin fed birds indicating anaemia. Serum total protein, albumin, globulin and albumin/globulin ratio decreased significantly (P< 0.01) in T-2 fed group. Serum glucose and cholesterol values decreased significantly (P< 0.01) in chlorpyriphos group. AST, ALT and ALP values increased significantly (P< 0.01) in T-2 and chlorpyriphos+T-2 groups. Chlorpyriphos fed birds showed increased ALT. Chlorpyriphos and chlorpyriphos+T-2 fed groups showed significant (P< 0.01) increase in serum amylase values. Decreased serum lipase values were observed in T-2 and chlorpyriphos+T-2 groups. No significant differences were observed in values of blood urea nitrogen, creatinine, uric acid and GGT between the control and toxin treated groups. Chlorpyriphos and T-2 toxins affected functions of various organs in broiler chicken, the effect being less than additive.